Penentuan Akar Persamaan Non Linier Menggunakan Metode Iterasi Tiga Langkah Orde Delapan - Efendi, Muchni Illahi; Subhan, Muhammad (Journal of Mathematics UNP, 2023)
In determining the roots of non-linear equations can be solved analytically and numerically. Non-linear equations that are difficult to solve analytically can be solved by approaching them with numerical methods, namely the Newton method, the Ostrowski method, and the Bawazir method. However, this method is still slow in obtaining its roots because of its small convergence order. The Eighth Order Three-Step Iteration Method was formed because of the shortcomings of the existing 0methods. 0The purpose of 0this study is to examine the0 process of forming the formula of the Eighth Order Three-Step Iteration Method, develop the algorithm, and analyze the order of convergence. 0This type of research is basic research0. From the0 research results, the algorithm is used in computer programs. 0The convergence0 order 0of 0the Three-Step0Iteration0Method is eight, so this method is faster than Newton's Method, Ostrowski's Method, and Bawazir's Method.